2018
DOI: 10.1542/peds.2017-1026o
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure and Validity of Self-Report in Low-Income Women and Children in India

Abstract: BACKGROUND: There is limited validation of self-reported measures for secondhand smoke (SHS) exposure in low-and middle-income countries. We evaluated the validity of standard self-reported measures among women and children in urban India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although cigarette smoking during pregnancy and lactation has been linked to several adverse pregnancy outcomes, smoking during pregnancy is still a prevalent behavior in many countries (Lange et al, 2018;Kondracki, 2019). In addition to active smoking, passive smoking (second hand smoke exposure) has been shown to have a high prevalence in low-and middleincome countries (Elf et al, 2018). Long-term direct and indirect CS-exposure (ETS, second hand smoking) causes a wide range of damaging health effects, including increased lung inflammation, protease activity, oxidant stress, and apoptosis (Gopal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cigarette smoking during pregnancy and lactation has been linked to several adverse pregnancy outcomes, smoking during pregnancy is still a prevalent behavior in many countries (Lange et al, 2018;Kondracki, 2019). In addition to active smoking, passive smoking (second hand smoke exposure) has been shown to have a high prevalence in low-and middleincome countries (Elf et al, 2018). Long-term direct and indirect CS-exposure (ETS, second hand smoking) causes a wide range of damaging health effects, including increased lung inflammation, protease activity, oxidant stress, and apoptosis (Gopal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to the World health Organization (WHO), over 80% of the world's 1.3 billion smokers live in low-and middle-income countries, and around 1.2 million deaths per year are attributable to ETS, worldwide. In addition, epidemiological studies have demonstrated high rates of ETS among the youth in these low-and middle-income countries (Wang et al, 2017;Elf et al, 2018). ETS contains the same range of tobacco smoke toxins as active smoking, therefore it is likely that ETS during pregnancy may also have important effects on fetal health.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in infants, with correlations from r=0.35 with plasma nicotine and number of days the infant was exposed to TSE, to a maximum of r=0.66 between hair nicotine and number of cigarettes smoked per day 27 . Another recent study found a large range of correlations, from -0.2 to +0.4, which were not statistically significant, between parent-reported measures and air and hair nicotine 28 . However, one study found higher and statistically significant correlations between maternal hair nicotine and parent-reported measures (r=0.46–0.74) 29 .…”
Section: Discussionmentioning
confidence: 87%
“…is possible to assess SHS exposure over a longer period compared to the other three methods. Finally, nail nicotine assessment is the fth method of analysis, which may vary with age [5].The importance of SHS has made researchers employ several approaches to assess SHS exposure, including the use of questionnaires as a popular method due to their low cost and non-invasive nature [9]. In this regard, Nondahl et al classi ed SHS exposure into three settings, that is, home, work, and social settings.…”
mentioning
confidence: 99%
“…They compared the results of their questionnaire with hair and saliva cotinine measurements and found a positive correlation between the questionnaire results and laboratory ndings [10]. Moreover, Elf et al compared the questionnaire results with hair nicotine ndings; in their questionnaire, they also included questions for children exposed to SHS [9]. SHS can both occur in children and adults.…”
mentioning
confidence: 99%